High Molecular Weight Polymer Promotes Bone Health and Prevents Bone Loss Under Salmonella Challenge in Broiler Chickens - Raehtz, Sandi; Hargis, Billy M.; Kuttappan, Vivek A.; Pamukcu, Rifat; Bielke, Lisa R.; McCabe, Laura R. (Frontiers in Physiology, 2018)
As a consequence of rapid growth, broiler chickens are more susceptible to infection, such as Salmonella. Infections can potentially lead to bone loss, bone breaks and ultimately chickens being culled. Previously, we have shown links between intestinal health and bone health and hypothesize that therapeutics that target the gut can promote bone health. Here, we examined bone density and microarchitecture changes in Salmonella infected chickens and assessed if treatment with a high molecular weight polymer known to benefit intestinal health, MDY, can prevent bone loss in the infected chickens. Broiler chickens were infected with Salmonella at 7 days old and treated with MDY from day 7-21 or from day 14-21. Chicken femur trabecular and cortical bone parameters were analyzed by microcomputed tomography at 21 days. Our results establish that salmonella infection causes bone loss and altered bone microarchitecture in the femoral neck but not prximal femur region. This is consistent with the femur neck being a site of fracture in chickens. We further demonstrate that MDY treatment effectively prevented broiler chicken bone loss when given chronically during infection or a week after infection. Cortical bone mineral density in Salmonella treated chickens was also increased by MDY treatment. Taken together, our studies demonstrate that oral MDY can be a cost-effective way to benefit broiler chicken skeletal health.